Whiskey Point, Geary County - Stowers, Sarah (Kansas State University, The Chapman Center for Rural Studies, 2012)
The lost town of Whiskey Point is located in Geary County, Kansas. It was an “Island” community known to cavalry soldiers for its saloons, brothels, and restaurants. The town disappeared after the Provost Marshall dumped barrels of whiskey into the lake. This study provides a history of Whiskey Point using photographs, newspapers, maps, and an interview with a local history buff and artifact retriever.
Sarah Stowers, “Whiskey Point, Geary County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/106.
Keywords: Geary County; Whiskey Point; Fort Riley; Marshall Air Field; Santa Fe Trail; West Point